MEMAHAMI JIHAD DALAM PERSPEKTIF ISLAM (UPAYA MENANGKAL TUDUHAN TERORISME DALAM ISLAM) - Rahman, Amri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Abstract: This research is aimed at understanding the Islamic perspective of jihad derived from The Holy Quran and hadits of The Prophet Muhammad peace be upon to him. It is a library research that is classified as expanded qualitative-descriptive research. The research found that Jihad term in the Holy Quran that means “hard work “ found in 33 verses. These verses have a broad meaning namely a totally hard work in all aspect of life. Despite it is undeniable that there is a verse using Jihad term that means a physical fighting or hold weapon to combat the enemy. But many other verses using Jihad term that means a hard work in universal meaning. Jihad in the Holy Quran has three meanings, namely: (1) carrying on a battle or combat an enemy,(2) fighting for conquering the devil (syaitan), and (3) trying hard to conquer our ego. Islamic religion teaches to maintain a peaceful life and prohibit all kind of destruction. So, term of terrorism is not found in Islamic teaching. Jihad is not synonym to terrorism because jihad is not an anarchy action but fully devoted to gain the bounty of Allah.